2020
DOI: 10.1002/jsfa.10242
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fat sources on the intramuscular and subcutaneous adipose tissue fatty acid composition, and consumer acceptability of lamb

Abstract: BACKGROUND Lamb diets can alter the fatty acid (FA) profile of muscle and adipose tissue, which may affect the sensory quality and consumer acceptability of the meat. In this study, lambs received one of four pre‐slaughter diets: a barley / maize / soya‐based concentrate (C), supplemented with a saturated fat source (Megalac®) (SAT), or supplemented with protected linseed oil (PLO); or a by‐product (citrus pulp / distillers’ grain / soya‐based) diet (BPR). Intramuscular FAs and adipose tissue branched‐chain FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
(102 reference statements)
2
2
0
Order By: Relevance
“…Similarly, proportions of C16:1 n-9, C20:1 n-9, C18:2 n-6, C18:3 n-3, and C18:4 n-3 were greater (p ≤ 0.036) in the BYP compared with CON lambs. Similar results were obtained by others when lambs were fed concentrates containing either corn DDGS [60] or dried citrus pulp [9,61,62]. The lack of differences (p = 0.251) between groups in the proportion C18:1 n-9 observed in our study agrees with the results of Kotsampasi et al [50], who did not observe differences in this FA in lambs fed destoned EOC, and it was attributed to both the low fat content of the EOC (2.91%, DM basis) and the low level of inclusion in the BYP concentrate (8%).…”
Section: Resultssupporting
confidence: 90%
“…Similarly, proportions of C16:1 n-9, C20:1 n-9, C18:2 n-6, C18:3 n-3, and C18:4 n-3 were greater (p ≤ 0.036) in the BYP compared with CON lambs. Similar results were obtained by others when lambs were fed concentrates containing either corn DDGS [60] or dried citrus pulp [9,61,62]. The lack of differences (p = 0.251) between groups in the proportion C18:1 n-9 observed in our study agrees with the results of Kotsampasi et al [50], who did not observe differences in this FA in lambs fed destoned EOC, and it was attributed to both the low fat content of the EOC (2.91%, DM basis) and the low level of inclusion in the BYP concentrate (8%).…”
Section: Resultssupporting
confidence: 90%
“…The lower n-6/n-3 in LD muscle, although not significantly, was achieved in lambs fed conventional and microencapsulated linseed oil, an effect that can be explained by enhanced C18:3 n-3. Similar results of lambs fed protected linseed oil were obtained by Gravador et al (2020). However, all the above results indicate that linseed oil is more effective in modifying the FA composition of LD muscle compared to the microencapsulated form.…”
Section: Meat Qualitysupporting
confidence: 81%
“…The content of a lamb's diet influences the composition and value of its tissues (36). Furthermore, several trials have indicated that numerous feeding approaches can facilitate the deposition of n-3 LC PUFA in muscle tissues in lambs, resulting in healthier meat (16,24,(37)(38)(39)(40)(41)(42). The use of vegetable seed oils in ruminant diets was found to increase energy and the level of UFA deposited in meat (43).…”
Section: Discussionmentioning
confidence: 99%